2023
DOI: 10.1111/jace.18955
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric properties of layered oxyselenides with 3d transition metal ions

Abstract: Layered oxychalcogenides have received extensive attention in the fields of magnetism, superconductivity, lithium battery, and luminescence due to their unique electronic, magnetic properties, and layered structure, among which layered oxyselenides have excellent and promising thermoelectric performance, such as BiCuSeO and Bi2LnO4Cu2Se2. Here, we successfully synthesized Sr2MO2Cu2Se2 (M = Co, Ni, Zn) and Sr2FeO3CuSe and investigated the thermoelectric properties at a wide temperature range (298–923 K). They h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 84 publications
(132 reference statements)
1
3
0
Order By: Relevance
“…Figure S1 show the lattice constants. The lattice constants of Sr 2 ZnCu 2 S 2 O 2 at x = 0 and Sr 2 ZnCu 2 Se 2 O 2 at x = 1.0 were in close agreement with previously reported values [13,14,17,18]. Also, the lattice constants proportionally increased with the amount of Se substitution as following to Vegard's rule [29,30].…”
Section: Crystal Structuressupporting
confidence: 90%
See 1 more Smart Citation
“…Figure S1 show the lattice constants. The lattice constants of Sr 2 ZnCu 2 S 2 O 2 at x = 0 and Sr 2 ZnCu 2 Se 2 O 2 at x = 1.0 were in close agreement with previously reported values [13,14,17,18]. Also, the lattice constants proportionally increased with the amount of Se substitution as following to Vegard's rule [29,30].…”
Section: Crystal Structuressupporting
confidence: 90%
“…For example, by changing the Ch site to Se, an increase in the electrical conductivity is expected, similar to that of LaCuChO. Recently, Yang et al reported a new layered oxychalcogenide, Sr 2 ZnCu 2 Se 2 O 2 , using a combination of spark plasma sintering [18]. Sr 2 ZnCu 2 Se 2 O 2 exhibited approximately 10 8 times higher conductivity than Sr 2 ZnCu 2 S 2 O 2 .…”
Section: Introductionmentioning
confidence: 95%
“…Introducing more than one type of anion in a solid state compound offers greater flexibility to control its chemical and physical properties, by taking advantage of the different electronegativities, sizes, polarizabilities, and oxidation states of diverse combinations of nonmetals. Among mixed-anion compounds, oxychalcogenides are the best known but even these remain underinvestigated: <1000 oxychalcogenides have been structurally characterized compared to >50 000 oxides . Based on the hypothesis that local coordination environments around metal atoms can become more asymmetric and that band gaps can be narrowed relative to oxides, oxychalcogenides have received considerable attention as candidates for optical and thermoelectric materials, among many applications. Another hypothesis is that multiple anions lead to complex changes in the electronic structure around active sites in oxychalcogenides used as catalysts for water splitting, so that they exhibit intermediate characteristics that balance the requirements of structural stability and electrochemical performance. …”
Section: Introductionmentioning
confidence: 99%
“…Due to the high-temperature endurance, chemical stability, non-toxicity, and abundance in earth, oxides are irreplaceable as thermoelectrics. [13][14][15][16][17] In n-type thermoelectrics, there were researches on ZnO, [18][19][20][21][22][23] CdO, [24] TiO 2 , [25,26] In 2 O 3 [27][28][29] -based simple oxides, and Bi 2 O 2 Se, [30,31] Bi 2 LnO 4 Cu 2 Se 2 , [32] Sr 2 MO 2 Cu 2 Se 2 (M = Co, Ni, Zn) [33] -based layered oxides, while the simple crystal structure providing few elemental sites to be tuned, and low symmetry of layered oxides resulting in low electron effective mass, [34][35][36][37][38] limited the enhancement of their electrical properties. Strontium Titanate (SrTiO 3 ) as a cubic phase perovskite oxide possesses high symmetry and high density of states near the conduction band minimum (CBM), thus having a relatively large density of states effective mass and outperforming power factors.…”
Section: Introductionmentioning
confidence: 99%